Regular Evaluation Analysis: A Catalyst for Successful Implementation of the 21st Curriculum Programme. - Saliu, A. Danlad (Advances in Social Sciences Research Journal, 2020)
Evaluation of curriculum is undertaken for the purposes of ensuring accountability, accreditation, and improvement, all of which are highly relevant to teaching and learning in institutions. If evaluation is to drive change, it needs to be able to influence teaching practice. Therefore, this article reviews the meaning of curriculum, curriculum evaluation, reasons for curriculum evaluation, functions and types of curriculum evaluation, instruments for curriculum evaluation, its challenges and suggested solution for future evaluation.